Supporting Deaf Student Communication Using Low Tech Augmentative And Alternative Communication: Mendukung Komunikasi Siswa Rungu Menggunakan Komunikasi Augmentatif Dan Alternatif Berteknologi Rendah - Astuti Astuti; Eka Sapti Cahya Ningrum (Universitas Muhammadiyah Sidoarjo, 2026)
General Background Communication competence represents a fundamental requirement for academic inclusion, but learners with hearing impairments frequently experience severe language deprivation without specialized support. Specific Background Inclusive elementary schools in resource-constrained, disadvantaged, frontier, and outermost regions often lack the digital infrastructure required for high-technology interventions. Knowledge Gap While previous studies highlight computerized solutions for autism in urban settings, evidence remains scarce regarding the application of non-digital visual tools for hearing-impaired learners within rural inclusive classrooms. Aims This Classroom Action Research investigates the application of non-digital visual supports to facilitate the receptive and expressive language abilities of a fourth-grade hearing-impaired learner. Results Following two intervention cycles utilizing color-coded visual boards and adaptive picture stories, receptive language understanding increased from 20.0 percent to 75.0 percent, while expressive language production ultimately reached 66.7 percent. Furthermore, classroom learning participation surged from 15.0 percent to 81.3 percent, alongside an 80.0 percent post-test achievement. Novelty This study provides a contextualized instructional framework that transitions hearing-impaired individuals from unstructured home signs to functional symbolic exchanges using exclusively affordable, non-digital visual materials. Implications Teachers and inclusive schools in resource-limited areas must adopt non-digital visual supports alongside systematic prompt fading and peer-mediated activities to ensure sustainable educational participation. Highlights Color coded visual boards and adaptive picture stories substantially raise classroom participation rates. Receptive and expressive language abilities progress significantly through systematic prompt fading and peer interaction. Non digital visual interventions provide sustainable instructional solutions for marginalized and resource limited educational regions. Keywords Hearing Impairment; Receptive Language; Expressive Language; Inclusive Classrooms; Resource Limited Regions